Equality of Educational Opportunities at Public Primary Schools in Argentina - Cecilia Adrogue (Arizona State University, 2013)
This paper assesses the degree of equality of educational opportunities across Argentina's public primary schools. The main finding is that there are inequalities between jurisdictions, but even greater inequalities within them, suggesting the existence of serious problems in the distribution of resources at the sub-national level. Following the recommendations of the specialized literature, estimates of school quality and measures of disparity in educational opportunity were calculated. While school differences were found across provinces, even greater discrepancies were found among public schools located within provinces, which are responsible for the provision of primary education. Most importantly, inequality among public schools is found to be associated with factors that are considered socially unacceptable, such as the student's socio-economic status even among schools financed by the same governmental unit.